Proteomic analysis of spinal dorsal horn in prior exercise protection against neuropathic pain - Binglin Chen; Jiabao Guo; Chan Gong; Chenchen Zhu; Yang Wu; Shengbo Wang; Yili Zheng; Haixia Lu (Scientific Reports)
Abstract Neuropathic pain (NP) is a complex and prevalent chronic pain condition that affects millions of individuals worldwide. Previous studies have shown that prior exercise protects against NP caused by nerve injury. However, the underlying mechanisms of this protective effect remain to be uncovered. Therefore, the purpose of this study is to investigate how prior exercise affects protein expression in NP model rats and thus gain comprehensive insights into the molecular mechanisms involved. To achieve this objective, 6-week-old male Sprague–Dawley rats were randomly assigned into three groups, named as chronic constriction injury (CCI) of the sciatic nerve, CCI with prior 6-week swimming training (CCI_Ex), and sham operated (Sham). The CCI_Ex group underwent 6 weeks of swimming training before CCI surgery, while the CCI and sham groups had no intervention. Mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) were used as the main observation indicators to evaluate the behavioral changes associated with pain. Tissues from the spinal dorsal horn of the rats in the three groups were collected at 4 weeks after operation. LC–MS/MS proteomic analysis based on the label-free approach was used to detect protein profiles, and volcano plots, Venn diagrams, and clustering heatmaps were used to identify differentially expressed proteins (DEPs). Gene Ontology (GO) annotations, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and protein–protein interaction networks were employed to explore the biological importance of DEPs. At 14, 21, and 28 days following CCI, CCI rats with prior exercise showed a significant increase in the MWT and TWL of the injured lateral hind paw compared with those without exercise. A total of 122 proteins with significant changes in abundance were detected after CCI surgery, and 55 proteins were detected in the comparison between the CCI_Ex and CCI groups. GO and KEGG enrichment analysis revealed that oxygen transport capacity and the complement and coagulation cascades may be the critical mechanism by which prior exercise protects against NP. Serpina1, DHX9, and Alb are the key proteins in this process and warrant further attention, as confirmed by the results of Western blot analysis. In conclusion, this study provides new evidence that active physical activity can accelerate the relief of hyperalgesia after NP. Proteomic analyses revealed the potential target proteins and pathways for this process, offering valuable data resources and new insights into the pathogenesis and therapeutic targets of NP.